La implementación del sistema de dinero electrónico y su incidencia en el actuar financiero de los usuarios de la ciudad de Loja, período 2017 - Sánchez Rivera, Fausto Segundo (2018)
This research is structured according to the provisions of the Academic Regulations of the National University of Loja, has a legal and conceptual framework that supports the study entitled: "The implementation of the electronic money system and its impact on the act financially in the users of the city of Loja, period 2017” The evolution of technology and the need to improve financial processes make it necessary to innovate and implement new electronic tools, such as electronic money, which seeks to achieve efficiency in financial transactions, providing them with greater security, speed, and above all, to make the financial system available to all socioeconomic groups. In the city of Loja, the mechanisms used for the implementation of the electronic money system, despite the fact that they were in accordance with the socioeconomic level of the users, did not achieve their purpose, in the same way the degree of acceptance of the electronic tool by of the community is low due mainly to the ignorance of the system, also the operator has the physical structure and technological capacity to operationalize the use of electronic money, in terms of incidence it is evident that the implementation of electronic money has affected users in a low level, because the services provided do not meet their needs, associated with this there are no necessary establishments that have the system incorporated, also the media have not allowed an adequate socialization.